PERLINDUNGAN KONSUMEN ATAS PEMBATALAN SEPIHAK ACARA BORN TO BEAT (BTOB) OUR DREAM FAN CONCERT - NIM. A1011211252, ASTI WAHDINI (Jurnal Fatwa Hukum, 2025)
Abstract Fan Concerts are one of the most popular events among K-pop fans in Indonesia, such as the Born TO Beat (BTOB) Our Dream Fan Concert in Jakarta. However, this event was unilaterally canceled by the promoter, resulting in losses for consumers who had purchased tickets. Consequently, consumer needs were not fulfilled, which violates Article 4 letters c and h of the Indonesian Consumer Protection Law (UUPK). The problem formulation of this study is to analyze the form of consumer protection and to identify the efforts that can be undertaken by consumers to obtain full refunds and compensation for other losses resulting from the cancellation of the Born TO Beat (BTOB) Fan Concert.This research employs a normative juridical method with a descriptive-analytical nature. The approaches used in this study include the statute approach, the case Approach, the conceptual approach. The data used are secondary data obtained from laws and regulations, as well as legal journals discussing legal protection for consumers. The data collection technique used in this research is literature study. The result of this research shows that consumers have not yet received full legal protection due to the cancellation of the BTOB Fan Concert. In this case, the promoter violated Article 4 letters (c) and (h) of the Indonesian Consumer Protection Law (UUPK). Ideally, consumers are entitled to accurate, clear, and honest information regarding the condition and guarantees of goods and/or services, as well as the right to receive compensation, reimbursement, and/or replacement if the goods and/or services received are not as agreed or not as they should be. The consumers, who suffered losses after purchasing tickets for the Born To Beat (BTOB) Fan Concert, took non-litigation measures to resolve the issue by filing complaints with the Consumer Dispute Settlement Agency (BPSK) and the National Consumer Protection Agency (BPKN). Keyword: Consumer protection, Default, Fan Concert Cancellation, Refund. Abstrak Fan Concert merupakan salah satu jenis acara yang sangat populer di kalangan penggemar k-pop di Indonesia, contohnya yaitu Fan Concert Born TO Beat (BTOB) Our Dream In Jakarta. Namun, acara ini dibatalkan secara sepihak oleh promotor, sehingga menyebabkan kerugian bagi konsumen sebagai pembeli tiket. Dengan demikian kebutuhan konsumen tidak terpenuhi berdasarkan pada pasal 4 huruf c dan h UUPK. Rumusan masalah pada penelitian ini adalah untuk menganalisis bentuk perlindungan konsumen serta mengetahui upaya yang dapat dilakukan konsumen untuk mendapatkan pengembalian dana penuh dan kerugian lainnya dalam pembatalan Fan Concert Born TO Beat (BTOB). Penelitian ini menggunakan metode yuridis normatif dengan sifat deskriptif analitis. Pendekatan yang digunakan dalam penelitian ini meliputi pendekatan perundang-undangan (statute approach), pendekatan pendekatan konseptual (conceptual approach). Data yang digunakan berupa data sekunder yang diperoleh dari peraturan perundang-undangan dan jurnal hukum yang membahas tentang perlindungan hukum terhadap konsumen. Teknik pengumpulan data penelitian ini dengan cara Studi Kepustakaan. Hasil dari penelitian ini adalah konsumen masih belum mendapatkan perlindungan hukum secara penuh akibat dari pembatalan Fan Concert BTOB. Hal ini, promotor melanggar pasal 4 huruf c dan h UUPK. Seharusnya, konsumen memperoleh hak atas atas informasi yang benar, jelas, dan jujur mengenai kondisi dan jaminan barang dan/atau jasa dan hak untuk mendapatkan kompensasi, ganti rugi dan/atau penggantian, apabila barang dan/atau jasa yang diterima tidak sesuai dengan perjanjian atau tidak sebagaimana mestinya. Lalu upaya yang ditempuh konsumen dalam hal ini membeli tiket Fan Concert Born To Beat (BTOB) yang mengalami kerugian diselesaikan diluar pengadilan melalui jalur non-litigasi, yaitu dengan melaporkan ke Badan Penyelesaian Sengketa Konsumen (BPSK) dan Badan Perlindungan Konsumen Nasional (BPKN). Kata Kunci: Perlindungan Konsumen, Pembatalan Fan Concert, Pengembalian dana, Wanprestasi.